The Relationship Between Reading Culture and Critical Thinking Skills of High School Students - Eni Agustina; Yulia Ayriza; Muhammad Fikri Aulia (Journal of Innovation in Educational and Cultural Research, 2024)
Background Reading culture has an important role in developing students' critical thinking skills, as reading activities can broaden their horizons and improve their analytical skills. By reading regularly, students can train their brains to think more sharply and structurally, thus improving the quality of their critical thinking. This study aims to collect empirical evidence or facts regarding the relationship between reading culture and critical thinking skills. The participants in this study were 77 students. This research design uses a quantitative approach with a correlational method. Data analysis was done using the Pearson correlation test. The results showed a highly significant relationship with a positive correlation level of 0.976, a very strong correlation, and a 95% confidence interval between 0.80 and 1.000. This study concludes that reading culture and students' critical thinking skills have a positive and significant relationship. The findings indicate that improving reading culture among students can contribute to developing their critical thinking skills, which has important implications for educational practices in improving the quality of learning in secondary schools.